2019
DOI: 10.1186/s12985-019-1232-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pathogenicity of Vero cell-attenuated porcine epidemic diarrhea virus CT strain

Abstract: BackgroundPorcine epidemic diarrhea virus (PEDV) has caused enormous economic losses to the global pig industry. Currently available PEDV vaccine strains have limited protective effects against PEDV variant strains.MethodsIn this study, the highly virulent epidemic virus strain CT was serially passaged in Vero cells for up to 120 generations (P120). Characterization of the different passages revealed that compared with P10 and P64, P120 had a higher viral titer and more obvious cytopathic effects, thereby demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Four-day-old CDCD pigs orally inoculated with 2 log 10 PFU of PC22A (140th-160th) showed low to moderate fecal viral RNA shedding titers, with mild villous atrophy (Lin et al, 2017a) (Table 2). Sixday-old conventional pigs orally inoculated with 6 log 10 TCID 50 of G2b PEDV CT (120th passage in Vero cells) showed mild diarrhea and moderate fecal viral RNA shedding titers, with mild villous atrophy (Wu et al, 2019). On the other hand, pregnant sows orally inoculated with G1a PEDV DR13 (100th passage in Vero cells) showed no clinical signs but high VN antibody levels in the colostrum (Song et al, 2007).…”
Section: Tablementioning
confidence: 97%
See 1 more Smart Citation
“…Four-day-old CDCD pigs orally inoculated with 2 log 10 PFU of PC22A (140th-160th) showed low to moderate fecal viral RNA shedding titers, with mild villous atrophy (Lin et al, 2017a) (Table 2). Sixday-old conventional pigs orally inoculated with 6 log 10 TCID 50 of G2b PEDV CT (120th passage in Vero cells) showed mild diarrhea and moderate fecal viral RNA shedding titers, with mild villous atrophy (Wu et al, 2019). On the other hand, pregnant sows orally inoculated with G1a PEDV DR13 (100th passage in Vero cells) showed no clinical signs but high VN antibody levels in the colostrum (Song et al, 2007).…”
Section: Tablementioning
confidence: 97%
“…In addition, PEDV variants of mild virulence, such as the S1 N-terminal domain (NTD)-Del variant, also occurred naturally (Su et al, 2018;Suzuki et al, 2016;Zhang et al, 2018a). PEDV strains fully adapted to Vero cells and serially passaged at least 70 times (with trypsin or GCDCA in the cell culture medium) tended to replicate less efficiently in the intestine of pigs (Chen et al, 2015;Kim et al, 2017a;Lin et al, 2017a;Sato et al, 2011;Wu et al, 2019) (Table 2) and elicited low serum PEDV-specific antibody titers (Lin et al, 2017a). Twelve-week-old pigs orally inoculated with 8.2 log 10 TCID 50 of G1a PEDV 83P-5 (100th passage in Vero cells) exhibited only intermittent fecal viral RNA shedding in 3 of 4 pigs (Sato et al, 2011).…”
Section: Tablementioning
confidence: 99%
“…On day 3 post-inoculation, the mean virus shedding in group 4 piglets was 10 4.51 -fold lower than that in the group 1 piglets. Previous studies have shown that viral shedding titers are highest from days 3 to 4 post-challenge, and on these days, pathogenic signs were the clearest [29][30][31][32]. On day 4 post-inoculation, piglets from each group were necropsied to observe the lesions in the small intestines (Figure 3C).…”
Section: Pathogenicity Of Pedv2 Passages In Neonatal Pigletsmentioning
confidence: 95%
“…The highly virulent epidemic virus strain CT was serially passaged in Vero cells up to 120 passages (P120), and P120 had a higher viral titer and better cell adaptability with more obvious cytopathic effects. In addition, P120 showed significant reductions in clinical symptoms with 100% survival rate in piglets [ 2 ].…”
Section: Pedv Vaccinesmentioning
confidence: 99%
“…PEDV mainly infects the porcine intestinal epithelial cells. Then, PEDV colonizing the intestines results in atrophy, necrosis, and shedding of intestinal villi, which affected the absorption of nutrients, leading to vomiting, diarrhea, weight loss, anorexia, and depression [ 2 , 3 ]. When PEDV is excreted into the environment with feces, the contaminated feces may result in a mass epidemic.…”
Section: Introductionmentioning
confidence: 99%